Long noncoding RNA BS-DRL1 modulates the DNA damage response and genome stability by interacting with HMGB1 in neurons - Min-Min Lou (Nature Portfolio, 2021)
Long noncoding RNAs (lncRNAs) are known to regulate the DNA damage response (DDR), however their role in the brain is less well studied. Here, the authors demonstrate a neuron-specific role for Brain Specific DNA-damage Related lncRNA1 (BS-DRL1) and show BS-DRL1 modulates DDR by interacting with HMGB1 in a cell-type specific manner.